Massive bilateral chylothorax post blunt trauma. (December 2017) - Kozul, Christina; Jassal, Karishma; Judson, Rodney
Abstract: Chylothorax caused by blunt trauma is extremely rare. We present a case of bilateral massive chylothorax post blunt trauma and a review of the literature regarding the identification and management of this rare diagnosis. An eighteen-year-old male was involved in a motor vehicle crash where he sustained multiple injuries including a right, moderate to large, haemopneumothorax, a small left haemopneumothorax, left T8, T9, L1 and L2 acute transverse process fractures and fractures of bilateral 11th ribs. An intercostal catheter was inserted on the right side which initially drained blood-stained fluid however milky colour fluid was noted to be draining 11 h post insertion. Further imaging revealed a left pleural effusion causing a mediastinal shift where, once drained, also revealed a chylothorax. The patient was managed conservatively with bilateral intercostal catheters and a no fat/low-fat diet. The patient was discharged day seven post removal of bilateral intercostal catheters.